Mixture deposition method for graphene quantum dots-based dye-sensitized solar cell. (1st February 2022) - Mahalingam, S.; Manap, A.; Lau, K.S.; Omar, A.; Chelvanathan, P.; Chia, C.H.; Amin, N.; Mathews, I.J.; Afandi, N.F.; Rahim, N.A.
Highlights: Adopting mixture method deposition in graphene-quantum dot-based dye-sensitized solar cell (DSSC). The mixture method aided in improving the affinity between the TiO2 photoelectrode and the sensitizers. The mixture method increased the electron lifetime and the charge collection efficiency of the DSSC. High surface potential (33.47 mV) of the premixed sample restricted the photogenerated electrons to go into a deep state, reducing back electron transfer. Mixture-based DSSCs exhibited a PCE of 3.01% and a high Jsc of 5.08 mA/cm 2. Abstract: Unambiguously layer by layer (LBL) assembly of graphene quantum dots (GQDs), and dye (GQDs/dye) on TiO2 photoanode is the traditional and straightforward approach in the fabrication of graphene quantum dot-cosensitized solar cells (QDSSCs). Unfortunately, limited light absorption and low affinity of GQDs to TiO2 surface shadow the advantages of LBL and constrain its practical application. Herein, a new strategy of mixture configuration (GQDs+dye) was investigated. The experimental results demonstrated that the mixture of GQDs+N719 exhibited the highest efficiency of 3.01%. The increased Jsc (5.075 mA/cm 2 ) and high charge collection efficiency (0.96) in the mixture sample indicated enhanced electron collection at TiO2 . The less -OH groups on TiO2 provide a good surface intact of GQDs and N719, thus increasing the affinity between the photoanode and photosensitizers. In addition to that, the high surface potential (33.47 mV) of the premixed sample restricted the photogenerated electrons to go into a deep state, reducing back electron transfer. Therefore, mixture assembly of co-sensitization is an effective approach for light-harvesting in QDSSC. Graphical abstract: Image, graphical abstract